2020
DOI: 10.5195/ijt.2020.6341
|View full text |Cite
|
Sign up to set email alerts
|

Veteran and Provider Satisfaction with a Home-Based Telerehabilitation Assessment for Wheelchair Seating and Mobility

Abstract: The objective of this project was to measure Veteran and provider satisfaction with a home-based telerehabilitation assessment for wheelchair seating and mobility. Forty-three Veterans were seen remotely at their place of residence by a provider, using a VA Video Connect synchronous videoconferencing system. Veteran and provider satisfaction were collected using the Telerehabilitation Questionnaire (TRQ). Mean individual TRQ scores for both Veterans and providers were significantly higher than the scale midpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The use of telerehabilitation for wheelchair evaluations is a relatively new area of study. Previous publications have examined the increasing trend of telerehabilitation services ( von Humboldt et al, 2022 ), the benefits of telerehabilitation services ( Lemaire et al, 2001 ), and satisfaction with telerehabilitation services ( Ott et al, 2020 ). However, a study has not yet analyzed the clinical and demographic characteristics of individuals utilizing telerehabilitation for new wheelchair evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of telerehabilitation for wheelchair evaluations is a relatively new area of study. Previous publications have examined the increasing trend of telerehabilitation services ( von Humboldt et al, 2022 ), the benefits of telerehabilitation services ( Lemaire et al, 2001 ), and satisfaction with telerehabilitation services ( Ott et al, 2020 ). However, a study has not yet analyzed the clinical and demographic characteristics of individuals utilizing telerehabilitation for new wheelchair evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an overall high level of satisfaction with AMD evaluations via telerehabilitation ( Ott et al, 2020 ) and similar effectiveness when compared to in-person evaluations ( Schein et al, 2010 ; Bell et al, 2020 ). However, there is a lack of understanding regarding which individual characteristics are conducive to telerehabilitation use for device evaluation.…”
mentioning
confidence: 93%
“…Other types of disabilities or chronic conditions that reported high satisfaction with telerehabilitation included Parkinson disease, 20 , 21 chronic heart failure, 22 esophageal cancer, 23 chronic obstructive pulmonary disease, 24 , 25 neurorehabilitation, 26 speech therapy, 27 dysphagia, 28 obesity, 29 stroke, 30 , 31 and physical therapy following knee or hip replacement 32 34 or wheelchair use or mobility. 35 , 36 In response to the COVID-19 pandemic in 2020–2022, several studies have continued to report good patient satisfaction with telerehabilitation for various disabilities. 37 – 40 These studies of telerehabilitation for nonvisual disabilities have shown perceived benefits for ease of attending appointments with decreased travel time, increased patient involvement and self-management, being in a familiar environment, involving family assistance and training, and better adherence to rehabilitation schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Remote assessment of transfer quality can help to continue the provision of health care to wheelchair users when access to in-person care is limited [ 14 , 15 ]. Such barriers to in-person care can include, but are not limited to, difficulties with transportation, living in rural areas, and financial burdens [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%